INFLATION AND ITS EFFECTS ON CONSUMER BEHAVIOR AND ECONOMIC POLICIES - Gafurdjan , Zakhidov (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
In Uzbekistan, inflation exerts a profound influence on consumer behavior and shapes the country’s economic policies. This article explores the unique dynamics of inflation in Uzbekistan, its impacts on consumer behavior, and the corresponding economic policy responses. Inflation alters the purchasing power of Uzbek consumers, impacting their spending patterns and savings decisions. As prices rise, consumers may prioritize essential goods and services, adjusting their consumption habits accordingly. Such shifts in consumer behavior have significant implications for businesses and market dynamics within the country. Understanding the interplay between inflation, consumer behavior, and economic policies is essential for policymakers and stakeholders in Uzbekistan to navigate the complexities of the economy effectively.